Kecerdasan Emosional, Kecerdasan Intelektual dan Kecerdasan Spiritual Terhadap Pemahaman Akuntansi Dasar Dengan Motivasi Sebagai Variabel Moderating: Emotional Intelligence, Intellectual Intelligence and Spiritual Intelligence on Basic Accounting Understanding With Motivation as Moderating Variable - Nuraini, Fitri (Journal of Accounting Science, 2017)
Basic accounting is very important as the beginning to understand the concept of accounting, if on the basis of it can not fully understand then for the next is also difficult. The concept of introduction accounting is very important, especially for new students, like a building or a house then introduction accounting is the foundation. This study examines the effect of emotional intelligence, intellectual intelligence and spiritual intelligence on basic accounting comprehension with motivation as a moderating variable. In relation to moderating variables, researchers in this case choose motivation as a moderator of the relationship between emotional intelligence, intellectual intelligence and spiritual intelligence with basic accounting comprehension. The population used in this study was 104 students of Accounting Study Program in Semester 1 and 3 of Muhammadiyah University of Surabaya. The sampling technique uses convenience sampling with sampling of 77. The study used Moderated Regression Analysis (MRA) analysis tool. The result of research shows that (1) emotional intelligence and spiritual intelligence have an insignificant effect on basic accounting comprehension, (2) intellectual intelligence has significant effect on basic accounting comprehension, (3) motivation does not moderate the influence of emotional intelligence, intellectual intelligence and spiritual intelligence toward understanding of accounting basic.